PERSEPSI SISWA TENTANG PERILAKU SOSIAL DALAM PACARAN (STUDI KASUS SISWA SMA AL ISLAM 1 SURAKARTA) - Wiyanti, Raafi' Hikma (ISSN.2252-8407)
PERSEPSI SISWA TENTANG PERILAKU SOSIAL DALAM PACARAN (Studi Kasus Siswa SMA Al Islam 1 Surakarta) Oleh : Raafi? Hikma Wiyanti Prodi Pendidikan Sosiologi FKIP UNS ABSTRACT This research aimed to find out and to find out the students of SMA Al Islam 1 Surakarta?s perception on social behavior in dating. The method employed in this research was descriptive qualitative with Case Study approach. The data source collected of primary data including interview with informant, and secondary data including observation and documentation study. The sampling technique used was Purposive Sampling. Technique of collecting data used was in-depth interview with 12 informants consisting of students who have never had dating and those who were having dating, teachers and dormitory management. The data validation was carried out using data triangulation and method. Technique of analyzing data used was an interactive model of analysis encompassing data collection, data reduction, data interpretation, and conclusion drawing. The result of research showed that the regulation concerning the prohibition of making dating in SMA Al Islam 1 Surakarta had been applied tightly by the school. Nevertheless, many students of SMA Al Islam 1 Surakarta still made dating beyond the school?s knowledge. From here, a different perception emerged concerning dating between the students who had never made dating and those who were making dating. The conclusions of research were 1) perceiving the social behavior in dating, the students of SMA Al Islam 1 Surakarta who were having dating had positive perception that dating is used as the media of entertainment, spending spare time, as sharing friend and the means of attracting more attention from someone rather than parents, while those who had never made dating perceive that dating is negative because it approaches to zina (any sexual act outside of marriage), distracts learning focus and wastes time, 2) the perceived social behaviors were role behavior tendency, behavior tendency in social relation, and behavior tendency in social relation, 3) the factors affecting the perception of SMA Al Islam Surakarta students on social behavior in dating that environment in which there were prohibition of dating and knowledge, namely religion. Keywords: Students? perception, dating social behavior